Relationship between Calcium Deposit Size with the Pain Intensity in Patients with Calcified Rotator Cuff Tendinitis - Indri Wijayanti; I Nyoman Murdana; Tirza Z. Tamin (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background: Calcified tendinitis is a disease characterized by calcification of multifocal cells mediated byliving tissue. Calcified tendinitis may occur due to the collection of calcium in the supraspinatus tendon pouchor may be spread between rotator cuff muscle fibers and bursa, it may not cause pain or may cause mild painor discomfort. The aim is to determine the correlation of calcium deposit size to the pain intensity in patientswith calcified tendinitis.Methods: Methods in this study was a cross-sectional study, twenty subjects, aged 50-70 years old, diagnosedwith calcified tendinitis rotator cuff through musculoskeletal ultrasonography examination.Results: No significant correlations were found between calcium deposit size and pain intensity using VAS,r=0.238, p=0.312.Conclusion : The size of the calcium deposit was not correlated with the pain intensity in rotator cuff calcifiedtendinitis patients. But further research is needed whether the location and form of calcium deposits affect thepain intensity in calcified tendinitis rotator cuff patients.Keywords: calcified tendinitis; calcium deposit size; pain intensity.